Krigagem Ordinária Aplicada à Precipitação Pluviométrica nos Estados do Rio Grande do Sul e Santa Catarina Ordinary Kriging Applied to the Rainfall in the States of Rio Grande do Sul and Santa Catarina - Pires, Carlos Alberto da Fonseca; Reis, Janete Teresinha; Dullius, Ângela Isabel dos Santos; Priesnitz, Mariane Camargo; Pereira, Maria João (Ciência e Natura, 2016)
The states of the South second (Rossetti, 2000) presents industrial development, but its economy dependent on agriculture. The agriculture and crop yields, in turn, depend on the occurrence of rainfall. The agriculture and crop yields, in turn, depend on the occurrence of rainfall. located on the south end are basically influenced by the confrontation between extratropical and intertropical atmospheric systems characterized as one frontogenetic region, occurrence of studies and spatial distribution of weather events have used geostatistics, which is associated with a technical class to analyze and infer values of a variable. Kriging is a geostatistical estimation process variable values distributed in space and / or time based on values when considered interdependent adjacent the variogram analysis. geostatistical estimates are generally higher than other numerical interpolation methods as make use of the variogram function. This study aims to characterize the climatic conditions of Rio Grande do Sul estimating values for variable monthly total precipitation, building representative maps of the spatial and temporal distribution of this variable in 1963 and 2012 using ordinary Kriging.